Invazivna aspergiloza pri nekonvencionalnih bolnikih - Perčič, Simona (Medicinski razgledi, 2013)
Infections with Aspergillus spp. are most typically associated with invasive pulmonary aspergillosis in immunocompromised patients. However, an increasing number of reports deal with unusual manifestations of invasive aspergillosis. In the lungs, this may take the form of chronic invasive pulmonary aspergillosis, bronchocentric granulomatosis or tracheobronchitis. A number of extrapulmonary infections have been noted, sometimes in immunocompetent individuals. Examples include vertebral osteomyelitis, primary cutaneous aspergillosis, prosthetic vascular graft infection, infective endocarditis, post-operative aspergillosis and aspergillosis in the intensive care unit. Invasive aspergillosis has a myriad of clinical presentations. It has been known for many years that in disseminated aspergillosis the fungus can grow in a hu ge variety of organs. However, the current clinical challenge is early detection of invasive aspergillosis isolated to unusual sites, sometimes even in immunocompetent individuals. The combination of early diagnosis, appropriate treatment with voriconazole, and careful consideration of adjunctive surgical therapy should improve the outcome of such patients.
Keywords: aspergiloza; invasive aspergillosis; nekonvencionalna obolenja; unconventional patients; diagnosis; glivične okužbe; diagnoza